A major trade-off between structural and photosynthetic investments operative across plant and needle ages in three Mediterranean pines. (21st December 2017) - Kuusk, Vivian; Niinemets, Ülo; Valladares, Fernando
Abstract: Pine ( Pinus ) species exhibit extensive variation in needle shape and size between juvenile (primary) and adult (secondary) needles (heteroblasty), but few studies have quantified the changes in needle morphological, anatomical and chemical traits upon juvenile-to-adult transition. Mediterranean pines keep juvenile needles longer than most other pines, implying that juvenile needles play a particularly significant role in seedling and sapling establishment in this environment. We studied needle anatomical, morphological and chemical characteristics in juvenile and different-aged adult needles in Mediterranean pines Pinus halepensis Mill., Pinus pinea L. and Pinus nigra J. F. Arnold subsp. salzmannii (Dunal) Franco hypothesizing that needle anatomical modifications upon juvenile-to-adult transition lead to a trade-off between investments in support and photosynthetic tissues, and that analogous changes occur with needle aging albeit to a lower degree. Compared with adult needles, juvenile needles of all species were narrower with 1.6- to 2.4-fold lower leaf dry mass per unit area, and had ~1.4-fold thinner cell walls, but needle nitrogen content per dry mass was similar among plant ages. Juvenile needles also had ~1.5-fold greater mesophyll volume fraction, ~3-fold greater chloroplast volume fraction and ~1.7-fold greater chloroplast exposed to mesophyll exposed surface area ratio, suggesting overall greater photosynthetic activity. Changes in needle traits were similar in aging adult needles, but the magnitude was generally less than the changes upon juvenile to adult transition. In adult needles, the fraction in support tissues scaled positively with known ranking of species tolerance of drought ( P. halepensis > P. pinea > P. nigra ). Across all species, and needle and plant ages, a negative correlation between volume fractions of mesophyll and structural tissues was observed, manifesting a trade-off between biomass investments in different needle functions. These results demonstrate that within the broad trade-off, juvenile and adult needle morphophysiotypes are separated by varying investments in support and photosynthetic functions. We suggest that the ecological advantage of the juvenile morphophysiotype is maximization of carbon gain of establishing saplings, while adult needle physiognomy enhances environmental stress tolerance of established plants.